Morphofunctional description of diffuse lymphoid tissue of stomach fundal department’s mucosa at acute experimental gastritis, introduction of preparation «Platex-placental» and their united action. - Bilash, S. М. (Морфологія / Morphologia / Morfologìâ, 2012)
In research the features of localization and quantitative changes of immunocompetent cells of diffuse lymphoid tissue of stomach fundal department’s mucosa are studied at acute experimental gastritis, introduction of preparation «Platex-placental» and their united action. It is set, that at acute experimental gastritis an immune answer passes on a humoral type with activating of all cellular elements of diffuse lymphoid tissue. At introduction of preparation «Platex-placental» immunoreactions pass only in reply to preparation as heterograft, on the early terms of experiment. At introduction of preparation «Platex-placental» on a background of acute experimental gastritis immunoreactions in the stomach’s mucosa passed more tolerant and quicker.